Kashf wa-al-bayān fī ḥawādith al-zamān. - Ḥamawī, Muḥammad ibn ʻAlī, active 13th century, author.
1 online resource.
Keywords: This book is the first translated and annotated edition of Ibn Naf's Al-T'rkh al-Manr. Totalling 227 folios, the manuscript is a unique and valuable source full of historical accounts and anecdotes. The documents include two letters by the Emperor Frederick II in Arabic, as well as the only mention of the Albigensian Crusade in the Arabic language. Other notable material includes Ibn Naf's notes concerning the rivalries between the various Ayybids and the wars against Jall al-Dn Mangubirt, descriptions of the Ayybids in Yemen, and notes on the destruction of the Sicilian Muslims and the defeats of the Spanish Muslims. Containing an extensive historical introduction, this book will appeal to scholars and students interested in the later Crusader and middle Ayybid periods.